Pelatihan Penggunaan Laboratorium Virtual Berbasis PheT bagi Mahasiswa Calon Guru - Hidayatullah, Zul; Yahya, Yahya; Qusyairi, Muhammad; Sandi, Arnila (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
Virtual laboratories offer a great way to overcome the limitations of physical laboratories and make learning more interactive and meaningful in the modern era. Moreover, some schools have limitations in physical laboratories. On the other hand, teacher skills in managing and using virtual laboratories are still very minimal. Some teachers even do not know about virtual simulations such as PhET or livewire. The purpose of this community service activity is to improve the ability of prospective teacher students to utilize science learning technology through training using virtual laboratories created by PhET (Physics Education Technology). This PkM activity was carried out on prospective teacher students at Hamzanwadi University. The number of participants was 40 people and was carried out for 4 days. There are 3 core stages of PkM activities, namely the preparation stage, the implementation stage, and the evaluation stage. The results of the activity showed that participants better understood the functions and benefits of virtual laboratories. They are also better able to create inventive and technology-based science learning plans. Participants also felt satisfied and very satisfied with the training activities